2010
DOI: 10.1007/s12011-010-8933-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Toxic Risk Assessment of Arsenic in Male Subjects Through Drinking Water in Southern Sindh Pakistan

Abstract: The arsenic (As) hazardous quotient was estimated based on concentration of As in drinking water and scalp hair of male subjects of two age groups (n=360) consuming As contaminated water at different levels and non-contaminated drinking water. The total As concentrations in drinking water of less-exposed (LE) and high-exposed (HE) areas was found to be 3- to 30-fold higher than the permissible limit of the World Health Organization (2004) for drinking water, while the levels of As in drinking water of non-expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 53 publications
(71 reference statements)
1
11
1
2
Order By: Relevance
“…The understudied exposed subjects are mainly consuming fish in their diet (at least once a day) because they cannot use diversity of food items due to poverty. The contamination of water by As is probably more harmful to humans than As in food, because As bioavailability in water is generally higher than its bioavailability in food [24]. The concentration of arsenic in tissues of fish species (n=100) collected from the lake were found in the range of 2.11 to 14.1 μg/g, where As contents in tissues of fish species in the Indus river were observed in the range of 1.92-12.2 μg/g [7].…”
Section: Resultsmentioning
confidence: 99%
“…The understudied exposed subjects are mainly consuming fish in their diet (at least once a day) because they cannot use diversity of food items due to poverty. The contamination of water by As is probably more harmful to humans than As in food, because As bioavailability in water is generally higher than its bioavailability in food [24]. The concentration of arsenic in tissues of fish species (n=100) collected from the lake were found in the range of 2.11 to 14.1 μg/g, where As contents in tissues of fish species in the Indus river were observed in the range of 1.92-12.2 μg/g [7].…”
Section: Resultsmentioning
confidence: 99%
“…28 The victim had spent time in Pakistan where concentrations of inorganic arsenic in water from bore wells are elevated compared to the UK. 29,30 For example, in a report of 330 Pakistani subjects, the median urine concentration was 1.6 mmol/L in exposed individuals but these ranged up to 28.9 mmol/L (2166 mg/L). 31 In another study, urine concentrations as high as 24.6 mmol/L were found.…”
Section: Discussionmentioning
confidence: 99%
“…[4]. Among these groundwater contaminations, iron and arsenic are the most harmful which are present trace in amount, but have significant effects on drinking water and causes harmful impacts on human health in developing countries of South East Asia [5]. In developing countries, about 80% of the diseases are related to contaminated water and the resulting death 10 million per year [6].…”
Section: Introductionmentioning
confidence: 99%
“…About more than 20 million people drink water exceeding the national standard for arsenic levels [10]. Different studies have reported that inorganic arsenic has the risk of liver cancer, lung cancer, bladder cancer, skin cancer, prostate cancer and kidney cancer [3,5,8]. Arsenic has a non-carcinogenic effect due to its contamination in groundwater includes stomach pain, thickening, and discoloration of the skin, diarrhea, nausea, partial paralysis, vomiting numbness in hands and feet, blindness etc.…”
Section: Introductionmentioning
confidence: 99%